Frontal Sinus Drainage in Acute Pediatric Sinusitis With Intracranial Complications. Issue 6 (November 2021) - Chorney, Stephen R.; Buzi, Adva; Rizzi, Mark D.
Background: The indication for frontal sinus drainage is uncertain when managing pediatric acute sinusitis with intracranial complications. Objective: The primary objective was to determine if addressing the frontal sinus reduced need for subsequent surgical procedures in children presenting with acute sinusitis complicated by intracranial abscess. Methods: A case series with chart review was performed at a tertiary children's hospital between 2007 and 2019. Children under 18 years of age requiring surgery for complicated acute sinusitis that included the frontal sinus with noncontiguous intracranial abscess were included. Outcomes were compared among children for whom the frontal sinus was drained endoscopically, opened intracranially, or left undrained. Results: Thirty-five children with a mean age of 11.1 years (95% CI: 9.9-12.3) met inclusion. Most presented with epidural abscess (37%). Hospitalizations lasted 12.9 days (95% CI: 10.2-15.5), 46% required a second surgery, 11% required three or more surgeries, and 31% were readmitted within 60 days. Initial surgery for 29% included endoscopic frontal sinusotomy, 34% had a frontal sinus cranialization and 37% did not have any initial drainage of the frontal sinus. Groups were similar with respect to demographics, severity of infection, need for repeat surgery, length of stay, and readmissions (p > .05). Further, persistence of cranial neuropathies, seizures, or major neurological sequelae after discharge were no different among groups (p > .05). Conclusion: Drainage of the frontal sinus, when technically feasible, was not associated with reduced surgical procedures or increased complications and there is unclear benefit on measured clinical outcomes.